IDENTIFICATION THE ABNORMALITIES OF FLOWER AND FRUIT IN OIL PALM (Elaeis guineensis Jacq.) FROM TISSUE CULTURE CLONE AND D×P SUNGAI PANCUR VARIETY - Wulan Kumala Sari (Departement of Agrotechnology, Agriculture Faculty, Universitas Lampung, 2024)
Since the last few decades, plant propagation by tissue culture techniques have been developed for oil palm crops, but it often happens somaclonal variation that causes abnormal phenomena in oil palm flowers and fruits. Therefore, the purposes of this research were to identify the morphological characters of abnormal flowers and fruits, and to determine the types of abnormality of oil palm fruit derived from tissue culture cloned compared to D×P Sungai Pancur hybrid variety. This research was conducted at the educational field of Indonesian Oil Palm Research Institute (IOPRI) located in Sungai Dareh, Pulau Punjung Sub-district, Dharmasraya Regency, West Sumatra. The sampling method was purposive sampling and the observed data were presented descriptively. The results of this study indicated that abnormalities in oil palm fruit have been detected from the time of flower formation with the characteristic that when the flower blooms it forms more than seven carpels. The types of oil palm fruit abnormalities found at the study site were thin coat abnormalities, thick coat abnormalities, squirrel tail, mantle sissy and squirrel tail mantle sissy. In cases of mild abnormality, the oil palm fruit still has seeds and flesh, whereas in severe cases, the fruit only has a thin flesh and was completely seedless.